An Evaluation of Reporting Guidelines and Clinical Trial Registry Requirements Among Orthopaedic Surgery Journals. (7th February 2018) - Checketts, Jake X.; Sims, Mathew T.; Detweiler, Byron; Middlemist, Kevin; Jones, Jaclyn; Vassar, Matt
Abstract : Background: The responsibility for ensuring that studies are adequately reported is primarily that of those conducting the study; however, journal policies may influence how thoroughly authors choose to report their research. The use of reporting guidelines and prospective trial registration are promising avenues for ensuring that published studies adhere to the highest methodological standards. The purpose of this study is to evaluate orthopaedic surgery journal policies regarding reporting guidelines and trial registration, and to evaluate the effects that these policies have on adherence to reporting. Methods: We conducted a cross-sectional survey of journal policies and "Instructions for Authors" to determine the journals' policies and guidance regarding use of reporting guidelines and study registration. We also examined whether trials published in journals referencing CONSORT (Consolidated Standards of Reporting Trials) had higher rates of compliance with publishing a CONSORT flow diagram and whether journals with trial registration policies were more likely to contain registered trials than journals without these requirements. Results: Of the 21 orthopaedic surgery journals, 6 (29%) did not mention a single guideline, and clinical trial registration was required by 11 (52%) orthopaedic surgery journals and recommended by 2 (10%). Of the 21 general medical journals, 3 (14%) did not mention a single guideline, and trial registration was required by 13 (62%) general medical journals and recommended by 5 (24%) others. Furthermore, journals that referenced CONSORT were more likely to publish trials with a CONSORT flow diagram. Journals with trial registration policies were more likely to publish registered trials. Conclusions: Reporting guidelines and trial registration are suboptimally required or recommended by orthopaedic surgery journals. These 2 mechanisms may improve methodology and quality, and should be considered for adoption by journal editors in orthopaedic surgery. Clinical Relevance: Because orthopaedic surgeons rely on high-quality research to direct patient care, measures must be taken to ensure that published research is of the highest quality. The use of reporting guidelines and prospective clinical trial registration may improve the quality of orthopaedic research, thereby improving patient care.